Investigating the Role of Food-Derived Peptides in Hyperuricemia: From Mechanisms of Action to Structural Effects - Yu Han; Wanlu Liu; Kexin Li; Mingzhen Zhang; Xinqi Liu; Lu Li; Zhao Guo; He Li (Foods)
Hyperuricemia, a disorder of purine metabolism associated with cardiovascular disease, gout, and kidney disease, can be alleviated by food-derived peptides. However, the precise mechanisms remain unclear, hindering their development. This study reviews uric acid-lowering peptides from various sources, focusing on two pathways: inhibiting uric acid production and promoting excretion. Low-molecular-weight peptides (<1000 Da) exhibited superior uric acid-lowering effects. We further explored the relationships between amino acid composition and their target interactions. Peptides rich in cyclic amino acids (tryptophan, phenylalanine, and histidine) and containing small amounts of linear amino acids (leucine, cysteine, and glycine) demonstrated significant potential for lowering uric acid. These findings provide theoretical support for developing novel functional foods for the management of hyperuricemia.